Growth, yield and quality of strawberry by effect of the nutritional regime - Mixquititla Casbis, Gabriela; Villegas-Torres, Oscar Gabriel; Andrade-Rodríguez, María; Sotelo-Nava, Héctor; Cardoso-Taketa, Alexandre Toshirrico (Revista Mexicana de Ciencias Agrícolas, 2020)
The objective of the research was to determine the nutritional regime that favors the growth, yield and physical and biochemical quality of strawberries produced in hydroponics under plastic cover. In 2017, an experiment was carried out in the experimental field of the Faculty of Agricultural Sciences of the Autonomous University of the State of Morelos, in which 27 nutritional regimes made up of the combination of variations in the concentration of NO-3 in the vegetative phase (10, 12 and 14 meq L-1), H2PO4- in the reproductive phase (0.75, 1.00 and 1.25 meq L-1) and K+ in the fruiting phase (5, 7 and 9 meq L-1) were evaluated. Treatments were distributed in a completely randomized experimental block design with four replications per treatment. The experimental unit was a black polyethylene container (15.14 L), with red tezontle as substrate and a strawberry plant. The results indicated that strawberry plants produced in hydroponics with nutritional regimen showed a significantly different response in the relative content of chlorophyll, leaf area, dry biomass of leaves, flower diameter, length and equatorial diameter of the fruit, average weight of the fruit, yield. per plant and concentration of total soluble solids in fruit, depending on the concentrations of NO3-:H2PO4-:K+, in the vegetative, reproductive and fruiting phases, respectively. The nutritional regime of 10 meq L-1 of NO3- in the vegetative phase, 1 meq L-1 of H2PO4- in the reproductive phase and 7 meq L-1 of K+ in fruiting, is recommended for producing strawberry in hydroponics because it increased significantly the diameter of the fruit and the yield per plant.
Keywords: fruiting phase; reproductive phase; soilless crops; vegetative phase